Evaluation and computational design of Ni25Al25Co15Fe15Ti8Mn7Cr5 high entropy alloy using THERMOCALC - Olorundaisi Emmanuel; J Babalola Bukola; Anamu Ufoma S.; Teffo Moipone L.; Ogunmefun Anthony O.; Odetola Peter; Olubambi Peter A. (MATEC Web of Conferences)
There has been a global demand for cutting-edge materials characterized by exceptional high-temperature performance, lightweight, and cost-effective. This study provides accurate and reliable predictions that can aid in the understanding of the material’s phase and thermo-mechanical properties. The phase formation and total hardness of Ni25Al25Co15Fe15Ti8Mn7Cr5 High Entropy Alloy (HEA) was investigated using THERMOCALC software version 2021b with the TCHEA5 HEAs database. The result shows the presence of BCC, SIGMA, and HEUSLER phases. The activity of the alloying elements shows Ni and Al to be stable at high temperatures, implying that excellent mechanical properties are expected at high temperatures.